2020
DOI: 10.1101/2020.04.15.042333
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mixing and matching methylotrophic enzymes to design a novel methanol utilization pathway inE. coli

Abstract: 25One-carbon (C1) compounds, such as methanol, have recently gained attention as 26 alternative low-cost and non-food feedstocks for microbial bioprocesses. Considerable 27 research efforts are thus currently focused on the generation of synthetic 28 methylotrophs by transferring methanol assimilation pathways into established 29 bacterial production hosts. In this study, we used an iterative combination of dry and 30 wet approaches to design, implement and optimize this metabolic trait in the most 31 common c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…DHA can be further converted into dihydroxyacetone phosphate (DHAP) by the endogenous DHA kinase of E. coli (Figure 1). Previously, De Simone et al showed that a strain expressing mdh from A. garner and das from P. angusta exhibited a higher growth rate in minimal medium with methanol and xylose than that with xylose alone (De Simone et al, 2020). In that case, Xu5P was mainly derived from xylose, thus, it was not clear whether the cyclic XuMP pathway would be functional in sugar-free conditions.…”
Section: Construction Of the Hybrid Methanol Assimilation Pathway In ...mentioning
confidence: 99%
See 1 more Smart Citation
“…DHA can be further converted into dihydroxyacetone phosphate (DHAP) by the endogenous DHA kinase of E. coli (Figure 1). Previously, De Simone et al showed that a strain expressing mdh from A. garner and das from P. angusta exhibited a higher growth rate in minimal medium with methanol and xylose than that with xylose alone (De Simone et al, 2020). In that case, Xu5P was mainly derived from xylose, thus, it was not clear whether the cyclic XuMP pathway would be functional in sugar-free conditions.…”
Section: Construction Of the Hybrid Methanol Assimilation Pathway In ...mentioning
confidence: 99%
“…The hybrid methanol assimilation pathway can generate key glycolytic intermediate glyceraldehyde 3-phosphate (GAP) with only two enzymatic steps and the energy efficiency of the pathway is equal to the RuMP pathway when fructose-6-phosphate aldolase (Fsa) and transaldolase (Tal) are used for xylulose 5-phosphate (Xu5P) generation (Supplementary Table S1). Recently, De Simone et al demonstrated the first example of heterologous expression of Mdh and Das in E. coli and showed that methanol can be integrated into several intermediates in central metabolism when cells were cultured with methanol and xylose as co-substrates (De Simone et al, 2020). However, the engineered strain showed low incorporation of 13 C-methanol into the pentose phosphate pool and proteinogenic amino acids, indicating that the regeneration of Xu5P should be further improved to increase the efficiency of the cyclic XuMP pathway.…”
Section: Introductionmentioning
confidence: 99%